Stories of vampires - Stowell, Louie (Usborne Publishing Ltd London, 2010)
Three vampire tales for children ready to tackle longer and more complex stories. Young heroes and heroines meet pale and mysterious strangers. But whom should they trust And will they survive the night Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton.